2020
DOI: 10.1016/j.jtcme.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of Korean red ginseng on experimentally induced colitis and colon carcinogenesis

Abstract: Korean Red Ginseng (KRG) exerts chemopreventive effects on experimentally induced carcinogenesis through multiple mechanisms. In this study, we investigated effects of KRG on dextran sulfate sodium (DSS)-induced colitis and azoxymethane (AOM) plus DSS-induced colon carcinogenesis in mice. Male C57BL/6J mice were fed diet containing 1% KRG or a standard diet throughout the experiment. The mouse colitis was induced by administration of 3% DSS in drinking water for 1 week. DSS caused body weight loss, diarrhea, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have found that probiotics supplementation could restore the structure of gut microbiota, thus enhancing intestinal mucosal barrier function and reducing gastrointestinal infection ( 88 ). Recent studies further proposed that restoring unbalanced gut microbiota was able to prevent the progression of IBD and intestinal cancer ( 89 ). Ginseng and ginsenosides are closely related to the role of gut microbiota, and various non-widespread initial ginsenosides have to be processed and transformed by gut microbiota before they get good biological activity ( 90 , 91 ).…”
Section: Effect Of Ginseng and Ginsenosides On Intestinal System Infl...mentioning
confidence: 99%
“…Previous studies have found that probiotics supplementation could restore the structure of gut microbiota, thus enhancing intestinal mucosal barrier function and reducing gastrointestinal infection ( 88 ). Recent studies further proposed that restoring unbalanced gut microbiota was able to prevent the progression of IBD and intestinal cancer ( 89 ). Ginseng and ginsenosides are closely related to the role of gut microbiota, and various non-widespread initial ginsenosides have to be processed and transformed by gut microbiota before they get good biological activity ( 90 , 91 ).…”
Section: Effect Of Ginseng and Ginsenosides On Intestinal System Infl...mentioning
confidence: 99%
“…Therefore, restoring the structure of gut microbiota is an important mechanism for the treatment of colitis. Ginseng has an anti-inflammatory and analgesic effects ( Lee et al., 2019 ) and it could prevent the colitis and related cancer induced by dextran sodium sulfate ( Shin et al., 2020 ). In the studies of dextran sodium sulfate (DSS)-induced SD rats, ginseng polysaccharides can significantly up-regulate the relative abundance of probiotics, reduce the relative abundance of pathogenic bacteria, and inhibit a variety of inflammatory signal pathways ( Shen et al., 2018 ; Wang et al., 2021 ).…”
Section: Ginseng Treats Various Diseases By Regulating Gut Microbiotamentioning
confidence: 99%